P2 Evaluation of Switching Therapy from Fixed-Dose Combination Inhaled Corticosteroid/Long-Acting Beta2agonist to Beclometasone Dipropionate/Formoterol (Fostair 100/6®). (19th November 2012) - Harris, T; Small, I; Price, D; Haughney, J; Ryan, D; Gruffydd-Jones, K; Ali, M; Musgrave, S; Brockman, J; Lavorini, F; Papi, A
Abstract : Introduction and Objectives: Asthma therapy reviews aim to minimise side-effects and achieve cost-effective asthma control. We set out to examine the impact of switching from a fixed dose combination therapy inhaled corticosteroid/long-acting β2 agonist (FDC ICS/LABA) therapy via dry power inhaler (DPI) or metered-dose inhaler (MDI) to beclometasone dipropionate/formoterol (BDP/FOR) via MDI at the same or reduced dose of ICS in stable patients. Methods: We utilised the UK's Optimum Patient Care Research Database to identify suitable primary care patients (aged 18–80 years) with asthma (diagnostic code and/or ≥2 asthma prescriptions in the last year) who were changed from FDC ICS/LABA to a prescription of BDP/FOR MDI at the same or lower BDP-equivalent ICS daily dose following a review of their existing ICS/LABA therapy. The number of exacerbations was measured as an outcome, with exacerbations defined as asthma related hospital, accident and emergency or out-of-hours attendance, GP consultations for lower respiratory tract infection and/or use of acute oral steroids (where asthma related includes all events with a lower respiratory Read code). All patients had 2 years of data: 1 year before and 1 year post therapy switch. Results: Out of a total of 365 patients, 334 had complete data for the analysis. 80 of these received a lower dose of BDP/FOR while 254 received an equivalent dose. In the year immediately before their therapy review, 69.5% (n=232) of patients had no exacerbations, compared to 76.9% (n=257) of patients following the review (p=0.075 Wilcoxon signed ranks). Prior to review, 20.4% of patients had 1 exacerbation compared with 12.0% of patients after the change, while 10.2% of patients had >1 exacerbation compared with 11.1% of patients following the review. Conclusion: These data suggest an increase in the number of patients not suffering from exacerbations and no deterioration in the number of exacerbations following the alteration in therapy. This indicates that BDP/FOR can be a valid therapy change in real-world patients on existing FDC ICS/LABA therapy.